An intervention of sustainable weight change: Influence of self‐help group and expectations - Kristina Carlén; Elisabeth Kylberg (Wiley, 2021)
Abstract Background Obesity is one of the most challenging public health problems in Western societies. Group activities are a way to empower individuals to make sustainable lifestyle changes. Self‐help groups enable individuals to share expectations and experiences on an equal basis. Objective The aim was to find a model for sustainable weight reduction for people with obesity and to evaluate the importance of expectations before entering the weight reduction programme. Methods Persons with a BMI >30 and aged over 30 years were recruited. Weekly seminars for 6 months with discussions concerning physical activity, eating habits and how to change one's lifestyle occurred. After the seminars, a self‐help group was initiated. The participants were encouraged to express their expectations before each step in the study. Results Our findings showed that those who had joined a self‐help group had reduced their weight significantly (−6.0 kg) compared with those who had not (−1.4 kg). Further, those who expressed a more mature expectation of the coming change in behaviour towards a healthy lifestyle showed slightly larger weight reduction (−6.1 kg) than those who expressed low expectations (−3.7 kg). Patient or public contribution Participants expressed their thoughts and views, which were considered and included in the programme. Conclusions Our findings indicate that the self‐help group can be an essential part of a weight reduction programme. The self‐help group is a novel strategy to strengthen sustainability in reducing weight. The study also highlights the importance of identifying behaviour change expectations before participating in a programme.